Autologous retransplantation for patients with recurrent multiple myeloma: A single‐center experience with 200 patients. Issue 13 (10th April 2013) - Sellner, Leopold; Heiss, Christiane; Benner, Axel; Raab, Marc S.; Hillengass, Jens; Hose, Dirk; Lehners, Nicola; Egerer, Gerlinde; Ho, Anthony D.; Goldschmidt, Hartmut; Neben, Kai
Abstract : BACKGROUND: Therapeutic options for patients with recurrent multiple myeloma after autologous stem cell transplantation (ASCT) include novel agents, conventional chemotherapy, or salvage ASCT with no standard of care. METHODS: A total of 200 patients with multiple myeloma who developed disease recurrence after treatment with upfront ASCT and received an autologous retransplantation as salvage therapy at the study center over a period of 15 years were retrospectively reviewed. The objective of the current study was to evaluate the role of salvage ASCT in terms of efficacy, particularly taking into account the impact of novel agents. RESULTS: The median progression‐free survival (PFS) and overall survival after salvage ASCT were 15.2 months and 42.3 months, respectively. The overall response rate (a partial response or greater) was 80.4% at day 100, excluding 6 patients who died before assessment. Factors associated with improved PFS and overall survival after salvage ASCT included an initial PFS of > 18 months after upfront ASCT, bortezomib‐containing or lenalidomide‐containing therapies for reinduction, response to reinduction, and an International Staging System stage of I before salvage ASCT. CONCLUSIONS: Salvage ASCT is capable of achieving sustained disease control in patients with multiple myeloma. The use of lenalidomide and bortezomib for reinduction has improved the results after salvage ASCT, suggesting that novel agents and salvage ASCT are complementary rather than alternative treatment approaches. Cancer 2013;119:2438‐2446 . © 2013 American Cancer Society . Abstract : Therapeutic options for patients with recurrent multiple myeloma after autologous stem cell transplantation (ASCT) include novel agents, conventional chemotherapy, or salvage ASCT with no standard of care. In the current study, the authors demonstrate that the use of lenalidomide and bortezomib for reinduction has improved the results after salvage ASCT in 200 patients, suggesting that novel agents and salvage ASCT are complementary rather than alternative treatment approaches